Utilization of Health Care Services and Willingness to Pay for Health Insurance in Kaski - Poudel, Shrijana; Ghimire, Gita Devi (Purbanchal University Health Journal, 2025)
Introduction: Health insurance is currently being considered as a mechanism for promoting progress to universal health coverage (UHC) in many countries. The government started the social health insurance program at selected health facilities. The accessibility and utilization of health insurance is important for quality care and to reduce financial burden to the care provider. Objective: The objective of the study was to assess Utilization of health care services and Willingness to Pay for Health Insurance in Kaski. Method: Descriptive cross sectional study design was conducted in Kaski district Pokhara. Cluster random sampling technique was adopted for selecting the subject. From each of the 30 clusters, 16 household were surveyed by using KPC field manual. The sample size was 477and Interview schedule was used to collect data. The data entered and analyzed by using computer software MS Excel and Statistical Package for the Social Sciences (SPSS2016). The quantitative variables were presented as mean and standard deviation, percentages and inferential statistics t test and chi-square test was used. Result: The study findings revealed that 60.4% involved in health insurance scheme for their health problem. Among them 52.1%utilize the health insurance. Overall mean and standard deviation of the satisfaction was 25.04±5.08. About 48% respondent had high level of satisfaction but only Thirty-five percent wants to renew the scheme. Level of satisfaction is associated with utilization and renew the scheme. Conclusion: Although more than half of the insured utilizes the scheme, the satisfaction should be improved through quality and efficient service by the hospital managers and service providers.